Componentes de la diversidad arbórea en bosques de pino encino de Durango, Méx. - Márquez Linares, Marco A.; González Elizondo, Socorro; Alvarez Zagoya, Rebeca (Instituto de Ecología, A.C., 2016)
Tree species and their relative importance were analyzed in terms of basal area per hectare in 235 sites of 500 m2 each, on three small watersheds of the Sierra Madre Occidental, Durango, México. Sixty-eight percent of the sites had 3 to 5 species, although species number ranged from 1 to 9. The two most common species at each site, Pinus teocote and P. durangensis, accounted for 83% of the total basal area, indicating that these species can be used to phisonomically characterize the forest from this region. In 88.4% of the sites, the first species occupied half of the total basal area, the second species occupied half of the remaining basal area, and so forth until the last species. This pattern was described using a geometrical mathematical model that can be useful to manage forest stands. Main species and plant associations were also described.